(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Listening seemed to be the most important subject because it affected communication directly. However, many students especially the juniors had many difficulties in listening subject. Thus, this study explored the difficulties in English listening of English majored juniors at Tay Do University. The participants were 50 students of English classes. A questionnaire was an instrument in the study. The result would point out the difficulties as background knowledge, vocabulary, pronunciation and accents, psychological obstacles in English listening of juniors majoring in English.